Adaptación marginal y ajuste interno en estructuras de zirconia-ytria elaboradas con los sistemas CAD/CAM procera® y cerec in-lab (2011)
ABSTRACT: The purpose of this in vitro study was to determine the marginal adaptation and internal fit in zirconia ytrya frameworks fabricated with Procera® and Cerec In-lab® CAD/CAM systems. Methods: fifteen prefabricated implant abutments were divided in three equally sized groups; noble metal alloy Pd-Au structures were then fabricated (control group), Procera® and Cerec In-lab YZ cubes® (n = 5). The marginal gap was determined by measuring 8 points around the abutment circumference taking the distance between the margin of the structure and the abutment. In order to determine internal fit, 8 measures were taken from the abutment´s external surface to the internal surface of the restoration. The measures were done with an optical microscope (50X). The data was the statistically analyzed using 1-way ANOVA, Student’s paired t test and Dunnett´test. Results: marginal adaptation mean for the control group was 18.24±4.81μm and Procera® 21.62 μm ±12.15 μm, while the average for Cerec In-lab® was 47.34 μm ±17.72 μm. The internal fit for the control group was 34,60 μm ±16.16 μm and Procera® group was of 118.67 μm ±50.84 μm in average and Cerec In-lab® 65.62 μm ±25.80 μm. Conclusions: the metal alloy and zirconia ytrya frameworks fabricated with Procera® and Cerec In-lab® CAD/CAM systems showed clinically acceptable marginal gap values. The internal fit values for metal alloy and Cerec® frameworks are within the ranges reported in the literature. While the mean for the Procera® group was 118.67 μm ±50.84, which is close to the internal fit maximum limit reported in the literature, there was no statistically significant difference when compared with the Cerec-In-lab® system.